Kemampuan Membawakan Acara dalam Pembelajaran Keterampilan Berbicara - Dedi, Fransisca S.O.; Frieska Maryova; Mas, Odi Nurisa Dwi (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2024)
Language is a system of sound symbols produced by the human speech apparatus and used to communicate something to the interlocutor. To communicate this language can be through spoken language and written language. Written language usually produces writing such as writing letters, writing essays, writing literary works and many more. Written language does not require the interlocutor to respond directly to what has been written. Meanwhile, spoken language is everything that is spoken and produced to get a response from the person you are talking to. In learning at school, students are required to be able to fulfill language skills. One of them is speaking skills. With speaking skills, students are expected to be able to communicate something well and correctly, using appropriate linguistic rules. To learn speaking, we can take material about hosting an event. Hosting an event must of course have excellent speaking skills. Because when presenting a program students are required to pronounce the words well. Place the high and low sound in words that need stress. Know the correct intonation when speaking and also pause words or sentences that have final intonation. In the field, it was found that students' speaking skills, especially in this case when presenting a program, were still unable to pronounce words correctly. Don't understand pauses and intonation when pronouncing words or sentences. Research was carried out with this title so that students were able to become a master of ceremonies or presenter as one of the language skills, namely speaking skills. The research results showed that speaking ability on a scale of 1 reached a score of 86 in the very good category.